Invention of a new Lin soft outer sheath as a continuous flow system for diagnostic flexible hysteroscopy - Bao-Liang Lin; Hsuan Chin; Midori Ookouchi; Takashi Takeda; Takeshi Suzuki; Kazunori Ueno; Sokichi Iwata (Wolters Kluwer Medknow Publications, 2015)
Objectives: This study aims to evaluate the efficacy of a newly developed Lin soft outer sheath that is used as a continuous flow system for outpatient flexible hysteroscopy. Materials and methods: Diagnostic hysteroscopy was performed in 134 patients who presented to our center with uterine bleeding over the 25-month study period. The flexible hysteroscope was equipped with a Lin soft outer sheath. Results: Hysteroscope insertion failure was observed in six cases of, i.e., an insertion failure rate of 4.5%. Out of the other 128 women, accurate diagnosis of four patients could not be made because of intrauterine blood clots, i.e., a success rate of 92.5%. No complication, except postprocedure bleeding for a few days, was encountered. Conclusion: The new Lin soft outer sheath is effective as a continuous flow system for outpatient flexible hysteroscopy.